Analysis of Teacher Job Satisfaction through Spiritual Intelligence and Emotional Intelligence in Palu, Central Sulawesi, Indonesia - Idris; Osman, Sharina BT (Universitas Pendidikan Ganesha, 2024)
Job satisfaction refers to the feeling of fulfillment and pleasure when expectations align with reality. A person's job satisfaction can be influenced by their intelligence, particularly spiritual and emotional intelligence. This study aims to describe the results of analyzing teacher job satisfaction through both spiritual and emotional intelligence, both individually and collectively, in Palu City. The research employed a survey method with a quantitative approach and multiple regression analysis. The population consisted of 417 teachers from public and private Madrasah Aliyah schools in Palu City, with a sample of 167 teachers determined using the Slovin formula. A Likert-scale questionnaire was used as the research instrument. The results indicate that both spiritual and emotional intelligence, both individually and together, have a positive and significant impact on teacher job satisfaction. Specifically, spiritual intelligence has a stronger influence (0.586) compared to emotional intelligence (0.315) on teacher job satisfaction. These findings suggest that both spiritual and emotional intelligence play a key role in enhancing teacher job satisfaction in Palu City, Central Sulawesi, Indonesia.